Decision Support System For Selection of Exemplary Employees at PT. Sinar Asia Perkasa - Syahriani Syahriani; Nurmah Nurmah; Luthfi Indriyani (Kresnamedia Publisher, 2020)
Sinar Asia Perkasa is a manufacturing company, where this company is always required to innovate and improve the quality and quality of its products. Because of this, the company PT. Sinar Asia Perkasa must improve itself to get employees who have high quality and work productivity. Employees are one of the most important parts of a company that must be managed properly. To get employees of the highest quality, a process is needed that can automatically provide recommendations in selecting exemplary employees at PT. Sinar Asia Perkasa, namely by establishing a Decision Support System. This Decision Support System is expected to assist in objectively selecting employees. Making this Decision Support System using the Profile Matching method with several criteria, namely aspects of the discipline, aspects of integrity, aspects of cooperation, and aspects of work performance. Then for the final stage of this method is ranking.